Case Report: Phloroglucinol-Induced Kounis Syndrome - Wu, Hao-Yu; Gao, Tian-Jiao; Cao, Yi-Wei; You, Peng-Hua (Frontiers in Cardiovascular Medicine, 2021)
Background: Kounis syndrome is an allergy-related acute coronary syndrome that is induced by various pharmacological and environmental factors. Given that many clinicians are not aware of this condition, many cases may be underdiagnosed. We report a case of type II Kounis syndrome induced by phloroglucinol. Case summary: A 52-year-old man with pre-existing coronary artery stenosis presented with a 30-minute history of chest pain and erythematous rash after intramuscular administration of phloroglucinol. An electrocardiogram demonstrated ST-segment elevation in leads II, III and aVF. Emergency coronary angiography revealed severe stenosis in the distal right coronary artery. Intravascular ultrasound showed plaque rupture and thrombosis, and the minimum lumen area was 3.0 mm2. A 3.5×38 mm stent was implanted in the distal right coronary artery. Troponin I levels were elevated. A diagnosis of type II Kounis syndrome induced by phloroglucinol was made, and the condition manifested as acute ST-segment elevation myocardial infarction. Conclusions: Clinicians should be aware of Kounis syndrome as a possible diagnosis in a patient who presents with chest pain and allergic manifestations given that an increasing number of triggers are being reported.